Proceedings of the 5th Universitas Ahmad Dahlan Public Health Conference (UPHEC 2019) 2020
DOI: 10.2991/ahsr.k.200311.044
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Profile About Anemia and Disparity Among Adolescent 15–24 years in Indonesia - 2012 and 2017

Abstract: Anemia in Indonesia is high. One of two pregnant women suffers from anemia as highest prevalence (85%) was among pregnant women aged 15-24. Maternal anemia are at risk of maternal death and giving birth to premature infant with low birth weight. Among age group 15-24 years, 32% is anemic (both men-women). The prevalence of anemia among women higher than men. The Ministry of Health has determined the consumption of iron tablet as nutrition program among adolescents, but only 8% of female teenagers who received … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 8 publications
(7 reference statements)
0
6
0
Order By: Relevance
“…Moreover, it lowers the immune system, making it susceptible to infection. If not treated properly, the high prevalence of anemia among adolescents will continue and contribute greatly to the incidence of anemia at the time of pregnancy [19,[23][24][25].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, it lowers the immune system, making it susceptible to infection. If not treated properly, the high prevalence of anemia among adolescents will continue and contribute greatly to the incidence of anemia at the time of pregnancy [19,[23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…Pregnant women are one of the groups most vulnerable to malnutrition because of the increased nutritional need to meet the needs of the mother and fetus. A wrong diet in pregnant women has an impact on the occurrence of nutritional disorders, including anemia [13, 24, 33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The previous analysis reported that young women aged 20-24 had a higher percentage of knowledge in urban areas. That percentage increased with education (Afifah et al, 2020). Other research in the United States also revealed that people living in rural areas tend to use search engines less than people living in urban areas and have less access to health information from various sources, including blogs, publications, and health workers.…”
Section: Sociodemographic Factorsmentioning
confidence: 96%
“…The high prevalence of anemia among young adults in Indonesia may differ among regions and population subgroups and is likely due to a combination of factors, including poor nutrition, infectious diseases, chronic diseases, inherited disorders (sickle cell anemia, thalassemia), and inadequate access to healthcare [ 4 , 5 ]. Interestingly, recent evidence has shown that the awareness programs and laboratory examinations have identified more thalassemia carriers, minors, or traits among young adults [ 6 ].…”
Section: Introductionmentioning
confidence: 99%